Characteristics of The Executive Authorities of The Largest Urban Centres in Poland After The Local Government Elections in 2024 - Krawczyk Dariusz (Management Systems in Production Engineering)
By decision of voters, the local government of the new term was elected in 2024. The study conducted in the largest Polish urban centres allowed to characterize single-person executive bodies of municipalities, taking into account both political and demographic criteria. The tendency to mask signs was confirmed. The level of social support for the winning candidates responsible for managing local administration for the next five years was also determined. The analysis covered all cities with district rights, whose total revenues reached 18% of the state budget revenues in the analysed period. 66 mayors who managed municipal employees and performed corporate supervision over municipal institutions, units and companies had the actual impact on the spending of these funds. Describing the single-person executive bodies of all Polish cities with district rights, elected in the elections in April 2024, was the purpose of the paper. The conducted research study allowed to characterize (taking into account both political and sociological criteria) a group of 66 mayors managing the largest centres of local government in Poland. The paper was based on the analysis of source materials from the National Electoral Commission, data provided by the Central Statistical Office, budget resolutions adopted by collegial decision-making bodies of cities with district rights, as well as media verification of texts published in the mass media and social media.